(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2016)
Men and women together complete the picture of social life. If novel is the mirror of society and if it has to depict social life in its entirety then it is but necessary to talk about both on equal terms. But society has traditionally been male dominated. Man has been hitherto been in forefront in almost in every field including literature. Woman was certainly presented in literary works but only according to male point of view and male perspectives. Female novelists began to emerge on the literary scenario of eighteenth century who tried to set forth their opinions. But it’s only Jane Austen who could accomplish this task.